The Case of Upper Karnali Hydroelectric Project - Shrestha, Hari Man (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
The Upper Karnali Hydroelectric Project, being one of the most attractive and suitable run-of-river hydropower projects for consumption of the energy in Nepal, should have been developed by Nepal for self consumption through self-construction and self-financing. The author describes that in Nepal things are not happening in a way to safeguard Nepal’s long-term national interest through deriving multiple benefits from modest and gradual way of utilization of better hydropower sites for own sake. Even the meager free entitlements are highly exaggerated in a falsified way to please India instead of striving hard for fulfilling its own need by own efforts.DOI: http://dx.doi.org/10.3126/hn.v16i0.12213  HYDRO Nepal  Journal of Water Energy and EnvironmentIssue. 16, 2015 January Page: 14-17 Upload date: March 1, 2015